2017
DOI: 10.2147/ijwh.s113416
|View full text |Cite
|
Sign up to set email alerts
|

Provoked vestibulodynia: current perspectives

Abstract: Provoked vestibulodynia (PVD) refers to vulvar pain of at least 3 months duration, localized to the vestibule, provoked by touch and sexual activity and occurring in the absence of a clear identifiable cause. The clinical spectrum ranges from mild with distressing discomfort through to severe and disabling pain. Current understanding is that PVD is one of many chronic pain conditions characterized by sensitization of peripheral and central nociceptive pathways, with pain arising due to dysfunctional neuronal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 89 publications
0
21
0
2
Order By: Relevance
“…Consistent with previous studies, many of our participants expressed positive responses to interdisciplinary vulvodynia treatment when they could access it, but such treatments were complicated by inconsistent care teams, a lack of specialists in the area, limited access to provincially funded therapists, or coming with a high private healthcare cost. 6 , 9 , 36 , 47 , 48 In addition, participants in our group suggested that even if such resources were available closer to home, they were unlikely to avail of them owing to the lack of anonymity in smaller communities.…”
Section: Discussionmentioning
confidence: 91%
“…Consistent with previous studies, many of our participants expressed positive responses to interdisciplinary vulvodynia treatment when they could access it, but such treatments were complicated by inconsistent care teams, a lack of specialists in the area, limited access to provincially funded therapists, or coming with a high private healthcare cost. 6 , 9 , 36 , 47 , 48 In addition, participants in our group suggested that even if such resources were available closer to home, they were unlikely to avail of them owing to the lack of anonymity in smaller communities.…”
Section: Discussionmentioning
confidence: 91%
“…Pelvic floor PT is also recommended in the treatment of interstitial cystitis 51 . If a patient with MPPS has accompanying vestibulodynia, the midwife can consider introducing dilators, with or without the help of pelvic floor PT, and medications such as lidocaine, topical estrogen and testosterone, and vaginal diazepam (this is an off‐label use of these medications) 52 . Finally, if pelvic organ prolapse is noted, a patient may benefit from a urogynecology referral along with pelvic floor PT.…”
Section: Treatment When Specific Pathology Is Involvedmentioning
confidence: 99%
“…To assess pain sensitivity of the pelvic floor muscles, single-digit pressure of approximately 2 kg (calibrated by an algometer just before the exam) was performed at the bulbocavernosus (at 5 o'clock and 7 o'clock), levator muscles (at 7 o'clock and 5 o'clock, respectively), and the perineal complex at 6 o'clock, as previously described. 28 A summary score (range 0−50) for static mucosal pain was generated by adding 5 numeric rating scale (NRS) scores (0−10) from cotton swab sensitivity tests at 10 o'clock, 7 o'clock, 6 o'clock, 5 o'clock, and 2 o'clock of the vestibule. A summary score (range 0−50) for muscular pain was generated by adding the 5 NRS pain scores (0−10) from pressure applied to the bulbocavernosus, levator complex, and the perineal body.…”
Section: Sensory Testing and Self-report Questionnairesmentioning
confidence: 99%
“…8 Recent investigations propose further tailoring treatment based on these associated factors-for example, psychological distress, 3,11,12 hormonal deficiency, 23 inflammatory markers, 9,15 presence of comorbid pain conditions, 9,34,35 or pelvic floor dysfunction. 28,31 Diagnostic criteria and examination recommendations for PVD have traditionally focused on the vestibular mucosa. However, recent evidence suggests that pain with vestibular contact may be inadequate to characterize penetration pain in women with PVD, as it disregards pain with pelvic floor muscle activation.…”
Section: Introductionmentioning
confidence: 99%